(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article deals with the problem of the adequacy of literary processing and translation of some fairy tales in Europe, as well as violations of moral principles in the author’s fairy tale. The analysis is based on the example of folk and literary tales and translations of folk tales in English.The material for the study became known folk tales: "Kolobok", "Ripka", a fairy tale "The Diary of a Killer Cat" by the English writer Anna Fine. By the XIX century, the fairy tale genre was largely folkloric, and with the development of Romanticism, attention to the fairy tale was greatly enhanced by philosophers, literary critics, and writers. In the nineteenth and twentieth centuries, literary treatments of folk tales appeared. During the analysis of a number of folklore and author’s tales, the facts of the change of genealogical and textual aspects were revealed, which leads to violations of the moral-ethical, didactic, informative components of the basic for the children’s age of the genre. The conclusion of this study is to emphasize attention to the problem of observing the genealogical features of the fairy tale by writers and translators. People engaged in this literary activity must have a deep and comprehensive understanding of the traditional and moral-ethical categories that are reflected in children’s literature. An adapter (writer, director, animator) and an adult reader must understand the content and moral essence of the fairy tale. Parents, teachers, educators should see in a fairy tale more than lightness and fantasy.